(3GdeKdK GdeJab GdeYfis - (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3CTQa eG fWb Hg GdeUOM GdeMOK hHYO , jbhd eMeO Hf jYbhH GdajQhRGHGOi gPG cJGH LeY LejY eG CWdb Ydjg ef GdcJH GdehVhYI ai GdeKdK s
(3BNQgG (B:s
(3hdjcf HGdjef GdNJGe Ydi MSH eG hbY ai GddZI hGdcdGe Hd de jcf ai GdHGH ZjQ eGVi KdGKi eaQO ef Ufa dg gPG GdcJGH GdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B200 s
(3eUOQ GbJfGA GdCUd (B:s
(3CeHQhRjGfG (B(195 x(2 )) s
Keywords: (3GddZIs